The Effect fo Ascending and 40 % Weight Training Method on The Strength of The Muscle Arm - Susanto, Nugroho Hery; Hartoto, Setiyo; Kartiko, Dwi Cahyo (Journal of Physical Education Health and Sport, 2018)
The purpose of this research is to increase performance softball UKM students with exercise ascending method and exercise 40% loads method. There is thirty-three students selected accordance will be conducted pretest to determine division of a group ascending, exercise 40% loads methodÂ  or the control group. Push up for 60 second to measure arm muscle strength level. Will be given exercise on 6 weeks for each group and treatment 3 times of a week. Test results paired sample t-test show a method of ascending significant influence on the variables strength of arm muscles, group of 40% loads methods significant influence on the variables strength of arm muscles. It can be concluded thatÂ  the exercise of ascending method and exercise of 40% loads methods effective to improve the components physical condition strength of arm muscles, this can happening because the duration less of exercise and high student activity, see the whole subject is a student of physical education who join on UKM softball UNESA.